Enhancing the Sport Spectatorship Market for Hearing-Impaired Audiences: Accessibility and Engagement Strategies - Niveditha Karthikeyan (Journal of Applied Sports Management, 2025)
This paper examines the application of the Americans with Disabilities Act (ADA) to the in-person sport spectatorship experience of hearing-impaired individuals. The delivery of the core sport product, especially at the stadium, is not equally accessible to individuals with disabilities, particularly for audience with hearing impairments. While the ADA mandates accessibility in public accommodations, its implementation for communication access within sport venues remains inconsistent. Through a focused review of legal frameworks, venue practices, and emerging technologies, the paper identifies gaps in current accessibility efforts and outlines practical recommendations to enhance inclusivity. Key strategies include the use of AI-powered real-time captioning, availability of sign language interpreters, and staff training. These measures not only fulfill ADA requirements but also represent an opportunity to engage a growing and underrepresented market of sport consumers.
Keywords: sport accessibility; hearing-impairment; sport spectatorship; fan engagement